Leading the strategic project within the organization and its stages of development - ABBAS DHAHIR ALRUMDHAN (Zien Journals, 2023)
As project management is becoming more strategic and business oriented, new and formal approaches are needed to address the changes in the profession. Strategic Project Leadership®1 (SPL) is a comprehensive, research-based approach to project management. It combines the strategic, business-related aspects of projects, the need to adapt a project to its unique level of innovation and context, the leadership perspective of inspiring and motivating the team, and the traditional needs of getting the job done. The main objective of SPL is to inspire project managers to be the business leaders of their projects and is giving them the tools to do that. In their new leadership role, they must deal with the strategic and business aspects of their projects, articulate a vision to inspire and motivate their teams, and learn how to adapt their management style to the right project and environmental context. This integrated, research-based, and industry-proven approach addresses the reality that most projects today are uncertain, complex, non-linear, and changing; and they must be managed in a dynamic and flexible way while, “one size does not fit all.” More important, it acknowledges the fact that meeting the ‘triple constraint’ of time, budget, and performance goals is insufficient to guarantee business success. Successful projects today require, in addition, the strategic and leadership perspectives, as well as considering the specific impact of innovation on each project. This paper starts by describing the shortcomings of traditional project management and addressing the context for building the SPL approach; it then outlines its major concepts, planning components, and managerial implications.
Keywords: Innovation; project management; project strategy; science and art of project management